Методи контролю безпечності м’яса та способи його збереження - Василишина, Ольга Василівна; Власенко, Ірина Георгіївна; Vasylyshyna, Olha; Vlasenko, Iryna (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: В статті розглянуто сучасні методи контролю хімічної безпечності м’яса. Показано, що для забезпечення якості та безпечності м’яса використовуються системи національного та міжнародного контролю, виробничі та інтегровані системи контролю. Контроль хімічної безпечності м’яса здійснюється за допомогою сучасних лабораторних методів аналізу, що дозволяють виявляти і кількісно визначати шкідливі речовини навіть у низьких концентраціях. Наведена характеристика цих методів, їх переваги та недоліки. Показано, що найбільш точними методами визначення хімічних забруднювачів у м’ясі є хроматографічні методи у поєднанні з мас-спектрометрією. Розглянуто сучасні біохімічні способи збереження якості м’яса, які використовують біологічно активні речовини, ферменти або корисні мікроорганізми, що пригнічують розвиток шкідливих бактерій і сповільнюють псування продукту. /// EN: The article considers modern methods of controlling the chemical safety of meat, their principle of action, advantages and limitations, and identifies the most effective approaches for laboratory analysis of food products. It is shown that to ensure the quality and safety of meat, national and international control systems, production and integrated control systems are used. The integrated use of laboratory control, automated monitoring and digital platforms is particularly effective in maintaining a high level of safety in meat and other food products. One of the most important components of safety is chemical safety. Control of the chemical safety of meat is carried out using modern laboratory analysis methods that allow the detection and quantification of harmful substances even in low concentrations. The main groups of such methods include chromatographic, spectroscopic, immunochemical and biosensor methods. The characteristics of these methods, their advantages and disadvantages are given. It is shown that the most accurate methods for determining chemical contaminants in meat are chromatographic methods in combination with mass spectrometry. They provide high sensitivity and specificity of the analysis. At the same time, enzyme-linked immunosorbent assay and biosensor methods are widely used for rapid screening, as they allow for the rapid detection of potentially hazardous substances in food products. Their combination provides comprehensive control over residues of veterinary drugs, toxins and contaminants. Modern biochemical methods of preserving meat quality are considered, which use biologically active substances, enzymes or beneficial microorganisms that inhibit the development of harmful bacteria and slow down product spoilage. Modern biochemical methods allow preserving meat quality naturally, increasing product safety and extending its shelf life.
Chemical methods of meat safety control and methods of its preservation
Keywords: хімічна безпечність мяса; системи контролю; хімічні забруднювачі; небезпечні речовини; методи хімічного аналізу; якість м’яса; meat safety; control methods; chemical safety; hazardous substances; meat quality